Post-Operative Rehabilitation in Ankle and Hindfoot/Midfoot Fusion and Reconstruction Surgery: A Scoping Survey of UK Foot and Ankle Surgeons and Allied Health Professionals. Issue 4 (22nd October 2020) - Houchen-Wolloff, Linzy; Calver, Rachel S.; Dudson, Chloe; Essop-Adam, Amirah; Mangwani, Jitendra
Category: Ankle; Hindfoot; Midfoot/Forefoot; Sports Introduction/Purpose: Ankle, hind and midfoot fusion/ reconstructive surgery is performed to treat a range of foot and ankle conditions. A prolonged period of immobilisation in plaster is usually advised following this type of surgery. More recently, there has been a paradigm shift in the management of Achilles tendon rupture/ ankle fracture rehabilitation with emphasis on early mobilisation. However there is little in the literature or guidelines on the post-operative rehabilitation for foot/ ankle reconstructive surgery, in particular, with regards to the period of immobilisation. The aim of this work was to scope the current practice of UK (United Kingdom) foot and ankle surgeons, and allied health professionals (AHPs) managing this patient group. Methods: An online survey (10 questions) was designed (using survey monkey) following a qualitative synthesis of published literature and sent to surgeons via BOFAS (British Orthopaedic Foot & Ankle Society) and AHPs via AFAP (Association of Foot & Ankle Physiotherapist & AHPs). Participants had 1 month to respond and reminder emails were sent out periodically by BOFAS/ AFAP. Results were collated via the online system and data were extracted in the form of tables and graphs. Raw data was also available to transfer to Excel for analysis. Free text responses were analysed using thematic analysis [10]. Data was coded manually to produce qualitative themes by 2 authors. Results: 117 surgeons and 55 AHPs responded and there was good agreement between the 2 groups. Almost 50% reported that they followed a local post-operative rehabilitation protocol. There was a wide variation in the time point when patients were instructed to weight-bear (2 weeks to >12-weeks). 57% reported that not all patients were routinely referred for post-operative rehabilitation. Non-union was a concern of early mobilisation as highlighted by 60% of the surgeons surveyed yet more than half (59%) believed that starting some weight-bearing at 2-weeks would reduce the risk of venous thromboembolism. Qualitative themes identified: treatment tailored to individual patients, lack of knowledge about the patient journey, treatment tailored to surgeon preferences, lack of a pathway, variation in practice (quotes in table 1). Conclusion: There is wide variation in the post-op rehabilitation of patients undergoing hind mid-foot surgery in the UK, with a lack of published research/ guidance in this area. Early rehabilitation could improve patient outcomes, yet the risk of non-union is a major concern. In recent years, there has been a paradigm shift in the management of Achilles tendon rupture and ankle fracture with an emphasis on early mobilisation, This is a treatment model we propose to replicate in hind/ mid-foot fusion populations. Further research in the form of a multicentre trial is warranted to inform international guidance in this area.